What 'difference' does a camera make? crime, youth, and representation in mid-century mexico city. Issue 2 (3rd April 2018) - Orisich, Shari
Abstract : This article examines the discourse on juvenile crime in mid-century Mexico City through an analysis of visual culture namely the nota roja genre of sensationalist press, and the role photography played in 'capturing' delinquency. Placing visual technologies like photography as more active players in nation-building, the article traces the social role of photography in shaping moral panics and public perceptions of crime. Not breaking entirely from its Porfirian past, I observe how elites and the new urban middle class conflated criminality with the clases humildes and saw the causes of delinquency in the 'degenerative' traits of the poor. In a time of rapid demographic change and the expansion of mass culture, tabloid representations of juvenile crime reflected anxieties around social reproduction and the fear of political instability. This photographic record of life in Mexico City reveals one way that capitalinos would come to 'see' social difference and youthful citizenship in the post-revolutionary period.